Systematic review of bioimpedance related to kidney problems and volume analysis (2024)
Chronic kidney disease (CKD) poses a significant public health challenge due to its high prevalence and serious implications for patients' health. In this context, bioimpedance stands out as an emerging tool with great potential for early detection and continuous monitoring of CKD. Through a systematic review based on the Scopus database and following a methodology adapted from PRISMA, this analysis delves into the use of BIA to assess hydration status in individuals affected by CKD. The meticulous search resulted in the identification of 505 relevant publications, including 28 reviews, 28 conference papers, 3 book chapters, 2 short surveys, and 2 editorials, highlighting a predominance of observational studies (85%) compared to randomized controlled clinical trials (15%). This research undersco,res a remarkable increase in interest and research on bioimpedance and CKD, particularly evident since 2019. Bioimpedance is validated as well as a valuable instrument for accurate assessment of hydration in patients with CKD, underscoring the imperative for further research to consolidate its usefulness in the early detection and, effective follow-up of this critical condition.